VCS655: Managements of Historical and Cultural Artefacts / College of Creative Arts - UiTM, College of Creative Arts (2023)
This course introduces cultural resource law and policies and the practices commonly employed in the management and preservation of these diverse and non-renewable resources. It covers a broad range of heritage resources, including historic building and structures, tradition cultural properties, archival material and human remain.